2012
DOI: 10.1002/jms.3126
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to hybrid ion trap/time‐of‐flight mass spectrometry coupled with liquid chromatography applied to drug metabolism studies

Zhao‐Ying Liu

Abstract: Metabolism studies play an important role at various stages of drug discovery and development. Liquid chromatography combined with mass spectrometry (LC/MS) has become a most powerful and widely used analytical tool for identifying drug metabolites. The suitability of different types of mass spectrometers for metabolite profiling differs widely, and therefore, the data quality and reliability of the results also depend on which instrumentation is used. As one of the latest LC/MS instrumentation designs, hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Early crystallographic results showed that the M 2 C 2 cluster normally exhibits a butterfly shape structure. [4][5][6][7][8] However, recently isolated carbide cluster metallofullerenes (CCMFs) have shown structural changes for relatively large M 2 C 2 @C 2n cages. 4,[9][10][11][12][13] Dorn and coworkers predicted that linear M 2 C 2 cluster structures should be observed for relatively large fullerene cages of at least 100 carbons.…”
Section: Structural Adaptability Of Internal Clustersmentioning
confidence: 99%
“…Early crystallographic results showed that the M 2 C 2 cluster normally exhibits a butterfly shape structure. [4][5][6][7][8] However, recently isolated carbide cluster metallofullerenes (CCMFs) have shown structural changes for relatively large M 2 C 2 @C 2n cages. 4,[9][10][11][12][13] Dorn and coworkers predicted that linear M 2 C 2 cluster structures should be observed for relatively large fullerene cages of at least 100 carbons.…”
Section: Structural Adaptability Of Internal Clustersmentioning
confidence: 99%
“…Isotopic tracing combined with online radioactivity detection and mass spectrometry is an effective modern analytical tool used to elucidate the metabolic and residue kinetics of the tested compounds in animals 19 . With its high resolution and mass accuracy, as well as reliable MS n capability, liquid chromatography/ion trap/time-of-flight mass spectrometry (LC/MS-IT-TOF) technology is being widely used for the identification of the structure of the unknown compounds 20 . In the present study, a stable 3 H-ADP was prepared by our group, and its metabolism, excretion, distribution, and elimination were systematically investigated in swine, broilers, carp, and rats after oral administration of 3 H-ADP (5 mg/kg b. w.) for a single or 7 days.…”
mentioning
confidence: 99%
“…The distinct advantages of a QqTOF are fast acquisition rate, wide mass range and high ion transmission efficiency. A hybrid between TOF and ion trap mass analyzers was released as an IT-TOF, which can retain ions in the acceleration chamber for multi-stage mass spectrometry (MS n ) and switch polarity at a high speed (Liu, 2012). Among all the currently available HRMS platforms, TOF-MS and QqTOF MS are the most widely used systems for studying human exposures to environmental chemicals from an exposome perspective (Table 1), as detailed in the later section.…”
Section: Advances In Analytical Tools For Profiling the Environmenmentioning
confidence: 99%